Pengaruh Aplikasi Quora untuk Meningkatkan Keterampilan Berbicara Transaksional Siswa Kelas II SMA Negeri 12 Makassar - Normayanti Jufri; Syahruddin Nawir, Muhammad; Azhar, Sophia (Universitas islam Negeri Alauddin Makassar, 2023)
ABSTRACT This research focuses on the students’ Transactional Speaking especially in group discussion. The purposes of this research are (1) To find out the effectiveness of Quora Application in improving students ‘transactional speaking skill. (2) To find out the factors effect of Quora Application in improving students ‘transactional speaking skill. In this research, the population was the second grade students at Senior High School 12 Makassar consist of 15 students from class XI IPA 2. The method of this study was a Mixed Method, the design of this study was explanatory sequential (QUAN-QUAL) design were quantitative data were collected first and more heavily weighted than qualitative data. Pre-experimental method was applied in this research with a group pre-test and post-test design. The instruments used to collect data were speaking test and questionnaire. The result of the research presented that the pre-test of the class got the mean score 5.6. after giving treatment the students’ got the mean score 11.73. The outcome of the data analysis revealed that there was a significant improvement in the students’ skill in transactional speaking after being taught using quora application. Subsequently, the result of one sample t-test were Sig. (2-tailed) = 0,000 < 0,5. Therefore The null (Ho) is therefore rejected and the alternative hypothesis (H1) is accepted. In addition, the qualitative result from the questionnaire showed there were 4 factors affecting the development of students’ transactional speaking skill in group discussion those are: teaching materials content, language items, method, and activities in the teaching process. Based on the result analysis, the researcher may conclude that using quora application is effective to improve the students’ transactional speaking skill in group discussion because the learning objective is achieved, that was the students’ can be active to discuss the topic in classroom and were able to discuss appropriately according to the standard procedures and ground rules of group discussion. Keywords: Quora Application, Transactional Speaking skill